Process design of unfermented puff semi-finished products based on milk whey - Никифоров, Радіон Петрович; Сабіров, Олександр Володимирович (Technology audit and production reserves, 2015)
It is proposed to use milk whey instead of water and citric acid in technology of unfermented puff semi-finished products, which is a valuable source of essential amino acids and is characterized by low industrial processing. Based on studies it is proved a positive effect of citric acid on the quality indicators of unfermented puff semi-finished products. Prototype has performance similar to semi-finished product using traditional technology in terms of flexibility and stretchability of dough for semi-finished product. The developed semi-finished product has a better performance than the traditional analog in terms of elasticity. Indicators of yield and humidity of ready semi-finished product have values that meet the demands of regulatory documents. Based on the obtained results it is developed the process of unfermented puff semi-finished products based on milk whey, which is characterized by low industrial processing.